ChemInform Abstract: Chemical Interaction at the Buried Silicon/Zinc Oxide Thin‐Film Solar Cell Interface as Revealed by Hard X‐Ray Photoelectron Spectroscopy. Issue 36 (9th September 2014) - Wimmer, M.; Gerlach, D.; Wilks, R. G.; Scherf, S.; Felix, R.; Lupulescu, C.; Ruske, F.; Schondelmaier, G.; Lips, K.; Huepkes, J.; et al., et al.
Abstract Review: 23 refs.